Effect of Long-Term Supplementation With Silkworm Pupae Oil on the Methane Yield, Ruminal Protozoa, and Archaea Community in Sheep - Thirumalaisamy, Govindasamy; Malik, Pradeep Kumar; Trivedi, Shraddha; Kolte, Atul Purushottam; Bhatta, Raghavendra (Frontiers in Microbiology, 2022)
Supplementation of lipid and oils is one of the efficient strategies to reduce enteric methane emission; however, high cost and adverse impact on fibre degradation restrict the use of conventional oils. Silkworm pupae, a non-conventional oil source hardly used for human consumption in India, could be one of the cheaper alternatives for methane amelioration. The objective of the study was to investigate the effect of long-term supplementation (180 days) of silkworm pupae oil (SWPO) with two distinct supplementation regimes (daily and weekly intermittent) on daily enteric methane emission, rumen fermentation and ruminal archaea community composition. Eighteen adult male sheep divided into three groups (n=6) using complete randomized design were fed on a TMR consisted 10.1% CP and 2.79 Mcal/kg ME. SWPO was supplemented at 2% of dry matter intake in test groups either in a daily (CON) or weekly intermittent regimes (INT), whereas no oil was supplemented in control group (CTR). The intake of DM (P= 0.155) and CP (P= 0.157) in CON and INT groups was similar to that of CTR; however, the energy intake (Mcal/kg) in test groups was higher (P<0.001) than in CTR. In the CON group, the body weight gain (kg, P=0.022) and average daily gain (g, P=0.024) were higher than the CTR. The daily methane emission in CON (17.5 g) and INT (18.0 g) groups was lower (P=0.008) than the CTR (23.6 g). The transient nature of the anti-methanogenic effect of SWPO was demonstrated in the oil discontinuation study, where the daily methane emission in a short period back to the pre-supplementation levels. The long-term supplementation did not induce any significant change in the rumen archaeal community, whereas minor species such as Group3b showed the differential abundance among the groups. Oil supplementation in test groups compared to CTR decreased (P<0.001) the numbers of total protozoa (x107cells/ml), Entodiniomorphs (x cells107/ml), and Holotrichs (x106 cells/ml). Though the supplementation of SWPO, either daily or weekly intermittent regimes was equally effective in reducing the methane emission, but daily supplementation due to the relatively higher body weight (P=0.022) and average daily gain (P=0.24) is recommended for the feeding in sheep.